Effect of the chloride ion as a hole scavenger on the photocatalytic conversion of CO2 in an aqueous solution over Ni–Al layered double hydroxides1. Issue 27 (21st July 2015) - Iguchi, Shoji; Teramura, Kentaro; Hosokawa, Saburo; Tanaka, Tsunehiro
<x xml:space="preserve">Abstract</x> The photocatalytic conversion of CO2 to CO using a Ni–Al LDH photocatalyst in an aqueous solution of NaCl was investigated. HClO was produced as an oxidation product of Cl− under photoirradiation.